2018
DOI: 10.1002/elps.201800083
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore sequencing: An enrichment‐free alternative to mitochondrial DNA sequencing

Abstract: Mitochondrial DNA sequence data are often utilized in disease studies, conservation genetics and forensic identification. The current approaches for sequencing the full mtGenome typically require several rounds of PCR enrichment during Sanger or MPS protocols followed by fairly tedious assembly and analysis. Here we describe an efficient approach to sequencing directly from genomic DNA samples without prior enrichment or extensive library preparation steps. A comparison is made between libraries sequenced dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 88 publications
0
27
0
Order By: Relevance
“…In their report on Nanopore DNA sequencing aboard the International Space Station, Castro-Wallace and colleagues found that 29 out of 83,332 reads (0.03%) from mouse DNA were derived from the mouse mtDNA [53]. In another study, Zascavage and colleagues relied on Nanopore long-read sequencing for mtDNA analysis [54]. They reported an average coverage of mtDNA reads that varied between 15 and 118 fold from a whole genome sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In their report on Nanopore DNA sequencing aboard the International Space Station, Castro-Wallace and colleagues found that 29 out of 83,332 reads (0.03%) from mouse DNA were derived from the mouse mtDNA [53]. In another study, Zascavage and colleagues relied on Nanopore long-read sequencing for mtDNA analysis [54]. They reported an average coverage of mtDNA reads that varied between 15 and 118 fold from a whole genome sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Through the pipeline for the rrn assembly, we realised that the indels rate during the strand-wise alignments was always higher than mismatches, likely an effect of the alignment parameters (see methods). Notwithstanding, close inspections of the alignments suggest that such indels are produced in homopolymeric regions (containing single or di-nucleotide repeats), a common failure during basecalling of nanopore data [21,26]. On the other hand, the final assemblies were recovered with less than 1% indels proportions when compared to database references, thus indicating they were drastically attenuated when compared to the strand-wise evaluation, and suggesting that assemblies have largely been improved to correct typical errors of nanopore data, and likely retaining the nucleotide changes (mismatches) linked to species/strains genetic variability.…”
Section: Discussionmentioning
confidence: 99%
“…In their report on Nanopore DNA sequencing aboard the International Space Station, Castro-Wallace and colleagues found that 29 out of 83,332 reads (0.03%) from mouse DNA were derived from the mouse mtDNA (44). In another study, Zascavage and colleagues relied on Nanopore long-read sequencing for mtDNA analysis (45). They reported an average coverage of mtDNA reads that varied between 15 and 118 fold from a whole genome sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%